Magnetron sputtered thin-film vertically segmented Pt-Ir catalyst supported on TiC for anode side of proton exchange membrane unitized regenerative fuel cells. (21st June 2019) - Kúš, Peter; Ostroverkh, Anna; Khalakhan, Ivan; Fiala, Roman; Kosto, Yuliia; Šmíd, Břetislav; Lobko, Yevheniia; Yakovlev, Yurii; Nováková, Jaroslava; Matolínová, Iva; Matolín, Vladimír
Abstract: Dependence on noble metal catalysts is considered to be the main factor which hinders wider commercialization of proton exchange membrane fuel cells (PEM-FCs) and water electrolyzers (PEM-WEs). One way of lowering the loading of Pt and Ir is by using thin-film techniques for their deposition onto the high-surface conductive nanoparticles. Another approach, which is convenient in applications where the complete cycle of electricity - > H2 - > electricity takes place, is merging the PEM-WEs and PEM-FCs into one bi-functional system – the unitized regenerative fuel cell (PEM-URFC). In accordance with the above mentioned conception, this paper revolves around unconventionally prepared bi-functional magnetron sputtered lower-loading Pt-Ir catalysts for the anode side of PEM-URFC. Two geometries of catalyst coated membranes (CCM) were compared, differing in relative positioning of individual Pt and Ir thin films sputtered on TiC-based support sublayer; the sandwich-like Ir/TiC/Pt structure and the co-sputtered Pt-Ir/TiC structure. Wide arsenal of analytical methods, ranging from photoelectron spectroscopy to electrochemical atomic force microscopy determined that co-sputtering of Pt and Ir leads to alloy formation, thus preventing iridium to fully electro-oxidize to IrOx which in turn helps to explain why sandwich-like Ir/TiC/Pt structure, with no alloy, outperforms the co-sputtered Pt-Ir/TiC CCM in both operational regimes despite having the exactly same noble metal loading. The PEM-URFC single cell with sandwich-like bi-functional anode catalyst yielded 31.8% of round-trip efficiency at 1 A cm −2 in comparison to 34.2% achieved by combination of single-purpose cells with more than double the loading of noble metals. Graphical abstract: Image 1 Highlights: Two thin-film systems were investigated for anode side of PEM-URFC; Pt-Ir/TiC and Ir/TiC/Pt. Ir/TiC/Pt performs better than Pt-Ir/TiC in both electrolyzer and fuel cell regimes. Ir within magnetron co-sputtered Pt-Ir alloy does not fully electro-oxidize to IrOx. Separation of Ir and Pt thin films by TiC sublayer is crucial for high performance. Lower-loading Ir/TiC/Pt performs comparable to state-of-the-art, high-loading anode catalysts.